Pengaruh Persepsi Siswa Tentang Pelajaran IPS dan Motivasi Belajar Terhadap Hasil Belajar Siswa - Dwi Novanca, Lulut; Onik Farida Ni'matullah; Dwi Fauzia Putra; Roni Alim Ba'Diya Kusufa (Jurnal Penelitian dan Pendidikan IPS, 2025)
The influence of students' perceptions about Social Sciences (IPS) lessons and learning motivation on elementary school (SD) students' learning outcomes is very significant in determining their academic success. The main objective of this research is to determine the influence of students' perceptions of social studies lessons and learning motivation on student learning outcomes at SDN 3 Mentaraman. This research is quantitative research with a correlational survey nature. The population in this study was all class V students at SDN Gugus 2 Donomulyo District, totaling 90 students. The sampling technique used in this research was total sampling. The type of instrument is a questionnaire. The data analysis technique uses multiple linear regression tests. Based on the results of the multiple linear regression test, it is known that students' perceptions about social studies lessons and learning motivation on student learning outcomes together have an influence on student learning outcomes as evidenced by a significant value of 0.000. The student perception variable about social studies lessons has a significant value of 0.307, meaning that students' perceptions about social studies lessons do not have a significant effect on learning outcomes. Based on partial regression testing, it is known that learning motivation has a significant value of 0.000. With this, learning motivation has a significant effect on learning outcomes, so the second hypothesis is accepted.